Analisis Efisiensi Pengelolaan Sampah di TPA Losari, Wonorejo, Selomerto, Wonosobo - Wirdati, Alvina Chusnul; Anggraini, Dian (MASALIQ, 2023)
This research aims to analyze the efficiency of waste management at the Final Disposal Site (TPA) Losari, Wonorejo, Selomerto, Wonosobo. TPA Losari is a strategic location for waste management in the Wonosobo region and is under the supervision of the Environmental and Forestry Agency of the district. The study was conducted through direct observation of the waste collection, sorting, and management processes at the TPA. The results indicate that the monitoring and coordination by the Environmental and Forestry Agency focus on responsible and sustainable waste management at TPA Losari. Organic waste is processed through sorting and natural decomposition, while inorganic waste is sorted by waste pickers to support recycling efforts. There is also specific management for medical waste, requiring careful handling. However, TPA Losari is currently facing a "waste emergency" due to excessive waste and inadequate facilities and infrastructure. Therefore, the research also notes future plans to transform waste into reusable products, such as processing organic waste into compost and non-organic waste into paving materials. In conclusion, this research provides an in-depth overview of waste management at TPA Losari, Wonosobo, and identifies the issues that need to be addressed to improve waste management efficiency in the region. The findings of this study are expected to serve as a basis for developing strategic measures to address the waste emergency and enhance environmental quality in the Wonosobo area.